The COVID-19 pandemic and the gender gap in newly created domains of household labor - Abromaviciute, Jurgita; Carian, Emily K. (Sociological Perspectives, 2022)
In this study, we draw on interview data from 62 matched different-sex, dual-career spouses raising young children to examine the mechanisms behind the gender gap in household labor during the COVID-19 pandemic. We argue that the pandemic represents a unique case of social uncertainty and an opportunity to observe how structural conditions shape the gendered division of household labor. We find that under the rapid social transformation imposed by the pandemic, gender serves as an anchor and orienting frame for couples with young children. We argue that the pandemic (1) expanded traditional gender expectations to new domains of household labor and (2) heightened the importance of gendered explanations for the division of labor that justified intra-couple inequality. Our findings suggest that the particular structural conditions that characterize different times of uncertainty work through slightly different mechanisms, yet produce the same outcome: gender inequality, with long-lasting and wide-ranging implications. © The Author(s) 2022.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; care; charge mentale; conciliation famille-travail; discipline; division sexuelle du travail; famille; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique; états-unis

Bijou de banlieue - Hébert, Sara (Éditions Marchand de feuilles, 2022)
« Dans cette autofiction, Sara Hébert puise dans l'imaginaire punk, le langage des meetings AA et les souvenirs du mariage de sa mère. De façon intime, touchante et combative, elle critique la positivité toxique, le mythe du prince charmant et la culture du travail sexiste. Elle espère, à travers ses tranches de vie, vous aider à reprendre confiance en vous, à repenser vos rapports aux patrons et à vous libérer des hommes-bouées. »-- Résumé de l'éditeur.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; arts; autofiction; canada; care; cours; discipline; har4600; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sofia; thématiques; travail; études littéraires